2022
DOI: 10.1038/s41598-022-18210-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential biological responses of adherent and non-adherent (cancer and non-cancerous) cells to variable extremely low frequency magnetic fields

Abstract: Extremely low-frequency electromagnetic field (ELF-EMF) induces biological effects on different cells through various signaling pathways. To study the impact of the ELF-EMF on living cells under an optimal physiological condition, we have designed and constructed a novel system that eliminates several limitations of other ELF-EMF systems. Apoptosis and cell number were assessed by flow cytometry and the Trypan Blue dye exclusion method, respectively. In vitro cell survival was evaluated by colony formation ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…Nevertheless, when the intensity reaches 200 µT, there is a propensity for bacterial development to accelerate during the cocoa bean fermentation process (Sudarti et al, 2022e), but an intensity of 300 µT effectively enhances the productivity of edamame fruit (Sudarti et al, 2023). Hence, our work demonstrates that the influence of being exposed to ELF magnetic fields can have either beneficial or detrimental effects, contingent upon the strength, duration of exposure, and biological attributes of cells (Nezamtaheri et al, 2022).…”
Section: Introductionmentioning
confidence: 75%
“…Nevertheless, when the intensity reaches 200 µT, there is a propensity for bacterial development to accelerate during the cocoa bean fermentation process (Sudarti et al, 2022e), but an intensity of 300 µT effectively enhances the productivity of edamame fruit (Sudarti et al, 2023). Hence, our work demonstrates that the influence of being exposed to ELF magnetic fields can have either beneficial or detrimental effects, contingent upon the strength, duration of exposure, and biological attributes of cells (Nezamtaheri et al, 2022).…”
Section: Introductionmentioning
confidence: 75%
“…In addition, the mentioned amplification mechanism should be capable of explaining frequency dependency of the observed phenomena in order of few hertz as it is frequently reported in experiments [31][32][33][34][35]. Our recent study reported different windows of effective frequencies for observed response including elevated intracellular ROS level, morphological changes, and cell death in different cell lines [36]. Given the fact that the frequency of the only oscillatory step in the original RPM scheme (S-T 0 interconversion) is on the order of tens of megahertz [37], observations in the range of few hertz indicate a non-trivial underlying amplification mechanism.…”
Section: Introductionmentioning
confidence: 86%
“…This inhibitory effect on remodelling has been studied as a treatment for dermatologic cancers. 44 Electrochemotherapy mediated by PEMF was found to have a 2-fold increase in drug uptake compared to traditional electrochemotherapy in rat melanoma models. 45 Furthermore, electrochemotherapy with PEMF was found to have comparable tumour growth delays to traditional chemotherapy.…”
Section: Late Stage Wounds and Variability Of Pemf Effectsmentioning
confidence: 96%
“…Yet tissues exposed to lower frequencies of PEMF (1mT) had decreased ROS levels. 44 Higher amplitudes of PEMF promoted tissue regeneration and increased pro-inflammatory cytokines such as IL-6, IL-10 and TGF-β. 42,43 However, lower PEMF amplitudes generated opposite effects and inhibited the same inflammatory mediators.…”
Section: Late Stage Wounds and Variability Of Pemf Effectsmentioning
confidence: 98%
See 1 more Smart Citation